Regional government competition - Chen, Yunxian (Routledge studies in the modern world economy, 2019)
"This monograph provides a coherent and systematic explanation of China's regional economic development from the perspective of regional government competition. It gives an almost unknown exposition of the mechanisms of China's regional economic development, with numerous supporting cases drawn from both China and elsewhere. This book is an invaluable resource for anyone interested to learn more particularly the development and transformation of China's regional economy from both the Chinese and global perspectives"--